Characterizing OXPHOS inhibitor-mediated alleviation of hypoxia using high-throughput live cell-imaging - Beerkens, Anne P M; Boreel, Daan F; Nathan, James A; Neuzil, Jiri; Cheng, Gang; Kalyanaraman, Balaraman; Hardy, Micael; Adema, Gosse J; Heskamp, Sandra; Span, Paul N; Bussink, Johan (Cancer & metabolism, 2024)
BACKGROUND: Hypoxia is a common feature of many solid tumors and causes radiotherapy and immunotherapy resistance. Pharmacological inhibition of oxidative phosphorylation (OXPHOS) has emerged as a therapeutic strategy to reduce hypoxia. However, the OXPHOS inhibitors tested in clinical trials caused only moderate responses in hypoxia alleviation or trials were terminated due to dose-limiting toxicities. To improve the therapeutic benefit, FDA approved OXPHOS inhibitors (e.g. atovaquone) were conjugated to triphenylphosphonium (TPP+) to preferentially target cancer cell's mitochondria. In this study, we evaluated the hypoxia reducing effects of several mitochondria-targeted OXPHOS inhibitors and compared them to non-mitochondria-targeted OXPHOS inhibitors using newly developed spheroid models for diffusion-limited hypoxia. METHODS: B16OVA murine melanoma cells and MC38 murine colon cancer cells expressing a HIF-Responsive Element (HRE)-induced Green Fluorescent Protein (GFP) with an oxygen-dependent degradation domain (HRE-eGFP-ODD) were generated to assess diffusion-limited hypoxia dynamics in spheroids. Spheroids were treated with IACS-010759, atovaquone, metformin, tamoxifen or with mitochondria-targeted atovaquone (Mito-ATO), PEGylated mitochondria-targeted atovaquone (Mito-PEG-ATO) or mitochondria-targeted tamoxifen (MitoTam). Hypoxia dynamics were followed and quantified over time using the IncuCyte Zoom Live Cell-Imaging system. RESULTS: Hypoxic cores developed in B16OVA.HRE and MC38.HRE spheroids within 24 h hours after seeding. Treatment with IACS-010759, metformin, atovaquone, Mito-PEG-ATO and MitoTam showed a dose-dependent reduction of hypoxia in both B16OVA.HRE and MC38.HRE spheroids. Mito-ATO only alleviated hypoxia in MC38.HRE spheroids while tamoxifen was not able to reduce hypoxia in any of the spheroid models. The mitochondria-targeted OXPHOS inhibitors demonstrated stronger anti-hypoxic effects compared to the non-mito-targeted OXPHOS inhibitors. CONCLUSIONS: We successfully developed a high-throughput spheroid model in which hypoxia dynamics can be quantified over time. Using this model, we showed that the mitochondria-targeted OXPHOS inhibitors Mito-ATO, Mito-PEG-ATO and MitoTam reduce hypoxia in tumor cells in a dose-dependent manner, potentially sensitizing hypoxic tumor cells for radiotherapy.
Keywords: Metabolic reprogramming; Live cell imaging; Spheroids; Hypoxia; Mitochondria-targeting; OXPHOS inhibitors